Social Media as a Pathway to Leisure: Digital Leisure Culture among New Mothers with Young Children in Taiwan - Ho, Ching-Hua; Cho, Yi-Hsuen (Leisure sciences, 2024)
Applying the uses and gratifications theory, we explored why new mothers with young children in Taiwan use social media for leisure and how their needs are met. Participants comprised 25 mothers aged 25 to 40 years. Data were obtained using narrative, semi-structured interviews. The results showed that the relationship between new mothers and social media in shaping their leisure lives is not additive, but interactive. Social media enables new mothers to engage in personal leisure and gain a sense of belonging. Additionally, new mothers tend to combine personal leisure with family leisure activities and rely on social media information on activities. Further, social media can also serve as a platform for mothers to obtain work achievement. The concept of goals should be considered while analyzing the relationship between users' motivations and actions.